Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

From descriptive digital twins to closed-loop intelligent agents: Adaptive biogeochemical management in river-reservoir systems - Honghong Guo; Ruopu Yuan; Tongtong Wang; Rong Li; Yijia Li; Yuhang Su; Haihan Zhang; Tinglin Huang (Water Research, 2026)

Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

Artificial womb technology: Progress, challenges, and future directions toward extrauterine gestation - Di Mao; Bingkai Su; Shujie Zhang; Jizhou Li; Lei Zhang; Xunsi Qin; Rong Li (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Spatial patterns and interspecific associations of Pinus kesiya and its main companion species in a natural forest, southwestern China - Liyuan Zhang; Rong Tang; Xiaobo Huang; Xinyu Li; Yuanyuan Yi; Shao Lei; Jianrong Su; Shuaifeng Li (Forest Ecology and Management, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Does the mobility-as-a-service platform alleviate traffic congestion in China? - Zhao Liu; Rong Song; Bin Su; Chen Li (Transportation Research Part D: Transport and Environment, 2026)

Surface interception and transport of 14C-labeled polystyrene nanoplastics by benthic marine organisms - Wenwen Song; Dongxu Li; Jun Zhang; Ziyun Huang; Hongjie Zhang; Changhong Liu; Aijun Miao; Yu Su; Rong Ji (Marine Environmental Research, 2026)

Geomorphic filtering of pollen signals across a reef-to-basin transect and its implications for paleoenvironmental reconstruction in the Xisha archipelago, South China Sea - Jiani Chen; Sui Wan; Wei Li; Yi Zhong; Rong Xiang; Xiang Su; Chuanxiu Luo; Dizhu Cai (CATENA, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Nutrient input strategies mediate the link of rhizosphere soil microbiomes with rice productivity: Based on a decade-long field experiment - Ning Su; Xiangmin Rong; Qiaorong Li; Yansong Xiao; Guixian Xie; Chang Tian; Yali Kong; Yuping Zhang; Gongwen Luo (Agriculture, Ecosystems & Environment, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Achieving sustainable rice production with reduced nitrogen fertilization through unlocking soil organic nitrogen mineralization by alleviating microbial carbon limitation - Ning Su; Xiangmin Rong; Yao Liu; Junru Li; Runjia Yin; Guixian Xie; Yuping Zhang; Gongwen Luo (Field Crops Research, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Effect of ciprofloxacin on performance, antibiotic resistance genes, and microbial communities in mesophilic anaerobic codigestion enriched with Methanosarcina and a recovery strategy after collapse - Bao-Shan Xing; Yong-Ning Feng; Su Li; Liguo Wan; Yi-Fan Wu; Xiaochang C. Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)